Comparison of the Local Tolerability to 5 Long-acting Drug Nanosuspensions with Different Stabilizing Excipients, Following a Single Intramuscular Administration in the Rat. (January 2018) - Chamanza, Ronnie; Darville, Nicolas; van Heerden, Marjolein; De Jonghe, Sandra
To investigate the effects of common nanosuspension-stabilizing excipients on the nature and temporal evolution of histopathological changes at intramuscular (i.m.) administration sites, 5 groups of 39 male rats per group received a single injection of 1 of the 5 analogous crystalline drug nanosuspensions containing 200 mg/ml of an antiviral compound with particle sizes of ±200 nm and identical vehicle compositions, except for the type of nanosuspension stabilizer. The investigated stabilizers were poloxamer 338, poloxamer 407, d -α-tocopherol polyethylene glycol 1, 000-succinate (TPGS), polysorbate 80, and polysorbate 80 combined with egg phosphatidylglycerol. Histopathology and immunohistochemistry revealed progressive inflammatory changes at the i.m. administration sites and the draining lymph nodes that differed according to the time point of sacrifice and the type of stabilizer. Although the overall time course of inflammatory changes was similar across the groups, differences in the nature, severity, and timing of the inflammatory response were observed between animals injected with poloxamer- or TPGS-containing nanosuspensions and those injected with formulations containing polysorbate 80. A more severe and prolonged active inflammatory phase, the presence of multinucleate giant cells, prolonged macrophage infiltration of the formulation depot, and more persistent histiocytic infiltrates in the lymph nodes were observed in the polysorbate 80–containing nanosuspension groups. Such vehicle-mediated effects could influence the overall tolerability profile of long-acting nanosuspensions.